Exploring the effects of Artificial Intelligence on Student Learning and Instruction in Educational Training Providers (ETPS) in Botswana - Nyamutswa, Tapiwa Oliver; Mhlanga, David; Ndhlovu, Emmanuel (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
The integration of Artificial Intelligence (AI) in higher education has gained global attention; however, its application in Botswana’s Educational Training Providers (ETPs) remains underexplored. This study investigates the effects of AI, particularly ChatGPT, on student learning and instructional practices. A PRISMA-guided systematic literature review was employed, using Boolean operators to retrieve 53 articles from Google Scholar, from which a sample of 9 highly relevant studies was selected for detailed analysis. Findings reveal that AI enhances personalised learning, improves instructional efficiency, supports research skills, and increases student engagement. However, challenges such as academic integrity risks, cognitive dependency, data privacy concerns, and infrastructural limitations persist. The study concludes that AI presents both opportunities and risks for Botswana’s higher education sector. It recommends the development of ethical frameworks, investment in digital infrastructure, and capacity building to ensure effective and responsible AI integration aligned with evolving educational demands.